One vs. Two Instruments for Redistribution: The Case of Public Utility Pricing - Doina Radulescu; Fabian Feger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We use data on 180,000 households in the Swiss Canton of Bern and the years 2008-2013 to analyse whether one instrument (the income tax) vs. two instruments (income tax and public utility pricing) are adequate for income redistribution. The results of our structural estimation show that under certai assumptions there is a role for redistribution through public good pricing markups and hence with two instruments being adequate for redistribution.
Keywords: D12; D31; H21; H22; H24; L51; L94; L98; 330